2017
DOI: 10.1016/j.jjcc.2016.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mid-term clinical outcomes between “complete full-metal jacket strategy” versus “incomplete full-metal jacket strategy” for diffuse right coronary artery stenosis with drug-eluting stents

Abstract: The mid-term MACE was significantly less in the c-FMJ group than in the i-FMJ group, indicating that c-FMJ stenting was a favorable strategy for the diffuse long RCA lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This method is termed “full-metal jacket” in revascularization for chronic total occlusion of the coronary artery. 15) The possibility that atherosclerotic plaque remains is lower than the intermittent protection of a dissected or stenotic site alone with a stent. Favorable long-term vascular patency may be achieved and ischemic complications can be prevented.…”
Section: Discussionmentioning
confidence: 99%
“…This method is termed “full-metal jacket” in revascularization for chronic total occlusion of the coronary artery. 15) The possibility that atherosclerotic plaque remains is lower than the intermittent protection of a dissected or stenotic site alone with a stent. Favorable long-term vascular patency may be achieved and ischemic complications can be prevented.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, because the retrograde coronary artery dissection is the most catastrophic complication in PCI [ 19 ], we might take a conservative strategy to avoid the retrograde coronary-aorta dissection. Moreover, complete full-metal jacket strategy is known to be better than incomplete full-metal jacket strategy in PCI for diffuse RCA stenosis [ 20 ]. Yano et al reported that the length of stent was not associated with long-term adverse events in IVUS-guided PCI using everolimus-eluting stents [ 21 ].…”
Section: Discussionmentioning
confidence: 99%